THE EFFECT OF MATERIAL CONTROL AND OPERATIONAL EFFECTIVENESS ON OPERATIONAL PERFORMANCE AT PT. DUTARAYA SEJATI IN MEDAN - Nasution, Umar Hamdan; Zahri, Cut; Herlia, Herlia (Universitas Dharmawangsa Medan, 2025)
This research aims to determine the effect of material control and operational effectiveness on operational performance at PT. Dutaraya Sejati in Medan. The type of data is quantitative and the data source for this research is primary data in the form of a questionnaire. The research population is employees at PT. Dutaraya Sejati in Medan during 2023 as many as 208 people and the sample studied was 137 using random sampling technique. The data analysis technique uses the multiple linear regression method. The partial research results show that material control has a partial effect on operational performance at PT. Dutaraya Sejati Medan because the value of tcount (10.472) > ttable (1.97769) or a significance value of 0.000 is less than 0.05. And operational effectiveness partially influences operational performance because the value of tcount (5.297) > ttable (1.97769) or a significance value of 0.000 is less than 0.05. The research results simultaneously show that the variables of material control and operational effectiveness have a partial effect on operational performance because the value of Fcount (140.293) > Ftable (3.06) or or a significance value of 0.000 is less than 0.05.PT. Dutaraya Sejati in Medan must pay more attention to operational effectiveness in improving operational performance, so that company employees can complete work within the time set by the company. Keywords: Material Control, Operational Effectiveness, Operational Performance